Higher macrophage inflammatory protein (MIP)-1α and MIP-1β levels from CD8(+) T cells are associated with asymptomatic HIV-1 infection - Cocchi, Fiorenza (The National Academy of Sciences, 2000)
To test the hypothesis that β-chemokine levels may be relevant to the control of HIV in vivo, we compared RANTES, MIP-1α, and MIP-1β production from purified CD8(+) T cells from 81 HIV-infected subjects and from 28 uninfected donors. Asymptomatic HIV(+) subjects produced significantly higher levels of MIP-1α and MIP-1β, but not RANTES, than uninfected donors or patients that progressed to AIDS. In contrast, β chemokines in plasma were either nondetectable or showed no correlation with clinical status. The high β-chemokine-mediated anti-HIV activity was against the macrophage tropic isolate HIV-1(BAL), with no demonstrable effect on the replication of the T-cell tropic HIV-1(IIIB). These findings suggest that constitutive β-chemokine production may play an important role in the outcome of HIV-1 infection.